Psychological complications of childhood chronic physical illness in Nigerian children and their mothers: the implication for developing pediatric liaison services - Meremikwu Martin M; Kuteyi Olugbenga B; Omigbodun Olayinka O; Bakare Muideen O; Agomoh Ahamefule O (BMC, 2008)
Abstract Background Pediatric liaison services attending to the psychological health needs of children with chronic physical illness are limited or virtually non-existent in Nigeria and most sub-Saharan African countries, and psychological problems complicate chronic physical illness in these children and their mothers. There exist needs to bring into focus the public health importance of developing liaison services to meet the psychological health needs of children who suffer from chronic physical illness in this environment. Sickle cell disease (SCD) and juvenile diabetes mellitus (JDM) are among the most common chronic physical health conditions in Nigerian children. This study compared the prevalence and pattern of emotional disorders and suicidal behavior among Nigerian children with SCD, JDM and a group of healthy children. Psychological distress in the mothers of these children that suffer chronic physical illness was also compared with psychological distress in mothers of healthy control children. Methods Forty-five children aged 9 to 17 years were selected for each group of SCD, JDM and controls. The SCD and JDM groups were selected by consecutive clinic attendance and the healthy children who met the inclusion criteria were selected from neighboring schools. The Youth version of the Computerized Diagnostic Interview Schedule for Children, version IV (C- DISC- IV) was used to assess for diagnosis of emotional disorders in these children. Twelve-item General Health Questionnaire (GHQ - 12) was used to assess for psychological distress in mothers of these children and healthy control children. Results Children with JDM were significantly more likely to experience DSM - IV emotional disorders than children with SCD and the healthy group (p = 0.005), while children with JDM and SCD were more likely to have 'intermediate diagnoses' of emotional disorders (p = 0.0024). Children with SCD and JDM had higher rates of suicidal ideation when compared to healthy control children and a higher prevalence of maternal psychological distress was found in their mothers when compared to the mothers of healthy children (p = 0.035). Conclusion The higher prevalence of emotional disorders and suicidal ideation among children with SCD and JDM points to a need for development of liaison services in pediatric facilities caring for children with chronic physical illness to ensure holistic approach to their care. The proposed liaison services would also be able to provide family support interventions that would address the psychological distress experienced by the mothers of these children.